Well man clinic in general practice. Issue 6412 (21st January 1984) - Marsh, G N; Chew, C
Abstract : The establishment of a well man clinic run entirely by a nurse in general practice showed an appreciable number of men to be hypertensive, smokers, or overweight; it also showed some previously undetected disease. Efforts were made either to treat or to counsel men in whom these findings were made. A well man clinic may have greater value than a well woman clinic.